ENT300 Fundamental of Entrepreneurship. Business Plan : Bar-Shark Gym / Mohd Rozamel Bin Rosman... [et.al] - Rosman, Mohd Rozamel; Ashek, Muhamad ‘Adli; Rasit, Klimsman Lenang; Sedah, Stanley; Hamad, Muhammad Akmal Fitrie (2015)
Our business name is Bar-Shark Gym. The business has been decided to be in the form of partnership, which consists of five partners in a team. The management team is headed by five professional level workers that will handle the management arid operation of this company in order to get the best quality of products such as our selected supplements and services for maximum profit arid ensure the healthy lifestyle of our customer. All partners participate in the business management. We agreed that Mohd Rozamel Bin Rosman is our General Manager, Muhd ‘Adli Bin Ashek as Marketing Manager, Klimsman Lenang Anak Rasq as Operation Manager, Stanley Anak Sedah as Administration Manager and Muhd Akmal Fitrie Bin Hamad as Financial Manager. The selection of Manager is based on experience, skills and ability. Our main business activity, The Bar-Shark Gym is a company that provides several ability equipment and the services such as gym instructor to the customers in area of Desa Ilmu, Samarahari Sarawak. We do operate a self-service workout which means that the customer that entered our gym can do their own routine. But we also provided an instructor to the newbie customers that needs help with their routine, our gym instructor will also help our customer to gain more spirit which is by motivating them and gives them some advice on a healthy lifestyle. Besides that, we also sell several types of supplement such as the Mass Protein which is for the people that have problem with their skinny body. This product is to ensure that the users can gain weight easily. Whey Protein is for the people that have already got shape of body but to make it more ripped and more shaped cut muscle. And lastly the Fat Burner, this product is to ensure that users can fasten up their fat burning process while working up in our gym. The company will start on 1st January 2015. The initial capital for Bar-Shark Gym is RM25, 000. The company is targeting total combined profits of RM 958, 673 by the end of three years. In order to achieve business vision and mission, Bar-Shark Gym has planned strategies to focus in the quality of the services and marketing plan as well as to reduce the price at optimum rate. The Operation Manager and other managers have been working hard to make sure Bar-Shark Gym can satisfy the customers as well as exceeding their expectation. Satisfaction of customers is the first priority. The management team will be leads by the General Manager and the other managed will help to assist. The General Manager is responsible in controlling, leading, organizing as well as plan the entire business. The Marketing Manager is responsible in preparing the marketing plan, which includes identifying the target market, determining the market size, identifying the competitors, determining the market share, developing sales forecast and marketing strategies. The operation of our business is controlled and monitored by the Operation Manager. Not only that, the Operation Manager will supervise the other managers that help the Operation Manager. This is where quality control will take place in order for the workers to work on schedule and to ensure that all of us are, working accordingly and treating the customers with good manners. The Administrative Manager is responsible for all jobs related to office administration. Finally, the Financial Manager will handle financial matters such as preparing budgets and financial statement for the expenses of each department. All the financial statement need to be taken care properly.